The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1371/journal.pone.0225545
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the vaginal microbiome of pregnant women with either Trichomonas vaginalis or Chlamydia trachomatis

Abstract: BackgroundAlthough the significance of the human vaginal microbiome for health and disease is increasingly acknowledged, there is paucity of data on the differences in the composition of the vaginal microbiome upon infection with different sexually transmitted pathogens.MethodThe composition of the vaginal bacterial community of women with Trichomonas vaginalis (TV, N = 18) was compared to that of women with Chlamydia trachomatis (CT, N = 14), and to that of controls (N = 21) (women negative for TV, CT and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The results of this study are similar to the already published ones where the higher prevalence of TV is found in a highly vulnerable population: people deprived of their liberty, sex workers, and populations with low socioeconomic indexes [ 2 , 4 , 8 , 9 ]. In this study, 71% of the women were observed to have a family income of less than 189.00 USD, which represents less than 20% of the average family income from the rest of Brazil [ 19 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study are similar to the already published ones where the higher prevalence of TV is found in a highly vulnerable population: people deprived of their liberty, sex workers, and populations with low socioeconomic indexes [ 2 , 4 , 8 , 9 ]. In this study, 71% of the women were observed to have a family income of less than 189.00 USD, which represents less than 20% of the average family income from the rest of Brazil [ 19 , 22 ].…”
Section: Discussionsupporting
confidence: 90%
“…Taking into account that most cases of TV are asymptomatic or have common symptoms among uninfected patients [19,22], increasing even more the number of underdiagnosis cases of the disease [10], it is imperative to carry out population screening and to implement information measures on the disease as well as more specific and precise diagnostic methods [19,22]. The results of this study are similar to the already published ones where the higher prevalence of TV is found in a highly vulnerable population: people deprived of their liberty, sex workers, and populations with low socioeconomic indexes [2,4,8,9]. In this study, 71% of the women were observed to have a family income of less than 189.00 USD, which represents less than 20% of the average family income from the rest of Brazil [19,22].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, a sub‐analysis of our data did not show any difference in pregnancy outcomes related to the detection and treatment of STIs in women before or after 20 weeks gestation [data not shown]. Furthermore, the complex interplay between HIV infection, STIs and the vaginal microbiome may also have a impact on pregnancy outcomes 45–48 . Unfortunately, our study cohort characteristics and data collected limit our ability to address these issues.…”
Section: Discussionmentioning
confidence: 82%
“…often results in infection with anaerobic bacteria, leading to bacterial vaginosis and, in pregnant women, to preterm labor. The bacterial flora of the vagina dynamically changes under the influence of many factors, including lifestyle, smoking, hygiene habits, sex life, menstrual cycle, hormonal contraceptives, HPV (Human Papillomavirus) infections, Trichomonas vaginalis, and Chlamydia trachomatis, but mainly due to changes in the hormonal status of women resulting from age and the aging process [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. The first significant changes in the bacterial environment of the vagina occur during puberty.…”
Section: Changes In the Field Of Microbiotamentioning
confidence: 99%